The music of Harry Freedman - Dixon, Gail Susan, 1936- (University of Toronto Press, 2004)
Harry Freedman has been an important and respected figure in Canadian music for over half a century, and his productivity as a composer has been both prodigious and eclectic. Born in Poland in 1922 and raised in Winnipeg, Freedman studied at the Royal Conservatory of Music and played English Horn with the Toronto Symphony Orchestra. He resigned in 1970 to become the orchestra's first composer-in-residence, and has created some 175 works in a wide variety of genres including symphonies, concertos, string quartets, operas, ballets, film scores, popular songs, and jazz pieces. In The Music of Harry Freedman, Gail Dixon investigates Freedman's music with a view to illuminating its underlying principles, stylistic development, and means of coherence. Representative works from Freedman's oeuvre have been selected for detailed analysis. The chronological presentation of these works facilitates a clear understanding of Freedman's compositional style in its dramatic evolution from the tentative serial explorations of his early works to the eclectic stylistic spectrum of his later years. The analytic discussion is supplemented by a large number of musical examples, as well as compositional sketches and working notes, some in the composer's own hand. Numerous interviews with Freedman yield additional insights into his approach and perspective. Dixon does a great service to Canadian culture with this analytic study of the music of a celebrated twentieth-century figure.